A Descriptive Study of Human Salmonella Serotype Typhimurium Infections Reported in Ontario from 1990 to 1997. (1st October 2003) - Ford, Michael W; Odoi, Agricola; Majowicz, Shannon E; Michel, Pascal; Middleton, Dean; Ciebin, Bruce; Doré, Kathryn; McEwen, Scott A; Aramini, Jeffery A; Deeks, Shelley; Jamieson, Frances; Ahmed, Rafiq; et al.
Abstract : BACKGROUND: Salmonella infections cause gastrointestinal and systemic diseases worldwide and are the leading causes of food-borne illnesses in North America (1-4). Salmonella serotype typhimurium (ST), in particular, is increasingly becoming a major public health concern because of its ability to acquire multiple resistant genes (5, 6). OBJECTIVE: To describe demographic, temporal and geographical distributions, and reported risk factors of nonoutbreak cases of ST reported to a surveillance system in Ontario. METHODOLOGY: Descriptive analyses were performed on data on salmonellosiscases reported in Ontario between 1990 and 1998. Direct age- and sex-standardized rates were computed, and temporal trend analyses were performed using simple linear regression and a general additive model with alocally weighted regression (LOESS) smoother. RESULTS: The mean annual rates of infections with all Salmonella serotypes and with ST were 27 cases per 100, 000 persons and 3.7 cases per 100, 000 persons, respectively. Males and children under five years of age had significantly higher rates of both ST and ST definitive type 104 (DT104) infections. There was also evidence of temporal clustering of all strains of Salmonella, with significantly more cases being reported during the summer. Significantly higher rates of ST DT104 were observed in urban areas compared with rural areas, suggesting potential differences in the geographical distribution of risk factors. CONCLUSIONS: Information on demographic, temporal and geographical distributions, and risk factors is critical in planning disease control strategies. Further prospective analytical observation studies are needed to gain a better understanding of the epidemiology of ST and ST DT104 in Ontario, which will better guide disease control decisions.